Induction of Multiple Drug Transporters by Efavirenz - Johanna Weiss; Melanie Herzog; Sonja König; Caroline Henrike Storch; Nahal Ketabi-Kiyanvash; Walter Emil Haefeli (Elsevier, 2009)
Efavirenz, an important component of human immunodeficiency virus 1 (HIV-1) therapy, causes substantial drug interactions as an inducer of cytochromes and the transporter ABCB1. So far its effect on the expression of other transporters is unknown. We therefore investigated the effect of long-term exposure of cells to efavirenz on expression of a large number of important drug transporters and on cell proliferation as a surrogate of intracellular availability. LS180 cells were used as a surrogate for the major site of drug interactions and Jurkat cells were used as a surrogate for the main target cells of HIV therapy. Cells were treated with efavirenz over 4 weeks and mRNA expression of drug transporters was repeatedly quantified. After 4 weeks, efavirenz significantly up-regulated the mRNA of ABCB1, ABCG2, ABCC2, ABCC3, ABCC5, and SLCO3A1 in LS180 cells and ABCG2, ABCC1, ABCC4, ABCC5, and SLCO2B1 in Jurkat cells. However these changes in transporter expression did not influence cell proliferation indicating that intracellular efavirenz concentrations were likely not altered. Efavirenz induces mRNA expression of several drug transporters critically modulating the kinetics of other drugs. While these expressional changes will most likely not influence the efficiency of efavirenz itself, they might change the effect of other co-administered drugs. Keywords:: efavirenz, transporter, induction, drug-drug interaction